2018
DOI: 10.1016/j.jtumed.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of balanitoside in streptozotocin-induced diabetic rats

Abstract: Objectives The objective of this study was to evaluate the therapeutic effects of balanitoside in diabetic rats. Methods Twenty-five rats were divided into five groups. Rats in groups 2 to 5 were treated with streptozotocin to induce hyperglycemia. In addition, rats in groups 1 and 2 received 1 mL of distilled water, whereas those in groups 3, 4, and 5 received 10 and 20 mg/kg balanitoside and 6 U/kg insulin, respectively, for 14 days. All rats were sacrificed on day 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
(9 reference statements)
2
4
0
Order By: Relevance
“…Similarly, in a previous study, livers from DM rats revealed disturbed hepatic architecture, pericentral sinusoidal dilatation, apoptosis, and lipid droplet accumulation in hepatocytes, in addition to signs of inflammation ( 44 ). Additionally, the degeneration of liver cells and the congestion of blood vessels with periportal fibrosis were reported in previous studies ( 48 , 54 , 55 ). Histopathological changes due to STZ administration observed in our study were similarly observed in previous studies ( 1 , 56 ).…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, in a previous study, livers from DM rats revealed disturbed hepatic architecture, pericentral sinusoidal dilatation, apoptosis, and lipid droplet accumulation in hepatocytes, in addition to signs of inflammation ( 44 ). Additionally, the degeneration of liver cells and the congestion of blood vessels with periportal fibrosis were reported in previous studies ( 48 , 54 , 55 ). Histopathological changes due to STZ administration observed in our study were similarly observed in previous studies ( 1 , 56 ).…”
Section: Discussionsupporting
confidence: 72%
“…The findings revealed elevated blood glucose levels after diabetes induction and a rise in the levels of liver enzymes (ALT and AST) in diabetic rat’s serum. The substantial rise in ALT and AST levels in diabetic control rats indicated that diabetes mellitus could cause hepatic damage, possibly due to the increase in protein concentrations associated with glucogenesis and urea production found in the diabetic state ( Makena et al, 2018 ). When compared to rats given 50 mg/kg fustin, rats given 100 mg/kg fustin reported a slight rise in ALT and AST levels, suggesting that fustin at 100 mg/kg could have therapeutic effects in the hepatocytes by lowering ALT and AST levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in ALP and ALT has been most closely associated with liver damage in metabolic disease evolution [12,13]. Increase in liver enzymes has shown to be directly correlated to the development of diabetes phenotype in rats [14,15]. Similar observations have been made in diabetic patients [16].…”
Section: Discussionmentioning
confidence: 68%